Magnetic nanoparticles for enriching lafil compounds as well as preparation method and application of magnetic nanoparticles

By covering the functionalized co -price organic framework material on the surface of the tetraonic oxidation triangular nanometer, the covalent -based organic framework magnetic nanoparticles are prepared, and the problem of richer in the amount of traces of Radfly compounds in complex samples has been solved. High -efficiency, fast adsorption and easy separation effect.

CN119350565APending Publication Date: 2025-01-24CHINESE ACAD OF INSPECTION & QUARANTINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411470997.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently enrich trace Lafite compounds in complex samples, and non-magnetic covalent organic frame materials have difficulties in separation and recycling.

Method used

Through the pre -synthetic modification method, the covalent -based organic framework magnetic nanoparticles with methyl -functional housing are prepared, and the tetraonic oxide triangle is used as the nucleus to achieve high -efficiency enrichment of the La Fei type compounds.

Benefits of technology

The efficient and enrichment of the traces of the traces of the trace in complex samples, fast adsorption speed, large adsorption capacity, and magnetic nanoparticles are easy to separate and reused, simple operation, green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FDA0005094685670000011
    Figure FDA0005094685670000011
Patent Text Reader

Abstract

The invention discloses covalent organic framework magnetic nanoparticles as well as a preparation method and application thereof, and the magnetic nanoparticles comprise a core body formed by ferroferric oxide; the shell covers at least part of the surface of the core body, and the shell is composed of a methyl-functionalized repeating unit as shown in a formula I which is described in the specification. The magnetic nanoparticles have the advantages of strong hydrophilicity, large specific surface area, large aperture and the like, and can realize efficient enrichment of trace rafil compounds in complex samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of analytical chemistry, and in particular to covalent organic framework magnetic nanoparticles and a preparation method and application thereof. Background Art

[0002] As a phosphodiesterase inhibitor, dalafil has become an important basis for the research and synthesis of new PDE-5 inhibitors due to its long half-life and good safety. With its large-scale investment and use, it has brought certain risks to food safety and human health. In order to detect trace dalafil compounds remaining in food and reduce the interference of complex matrices, it is very important to establish an efficient and sensitive sample pretreatment method.

[0003] Therefore, it is necessary to develop a functionalized magnetic nanoparticle material to achieve efficient enrichment of raffinate compounds in complex sample matrices. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a covalent organic framework magnetic nanoparticle, which has the advantages of strong hydrophilicity, large specific surface area and pore size, and can achieve efficient enrichment of trace raffinate compounds in complex samples.

[0005] It should be noted that the present invention is completed based on the following work of the inventors:

[0006] Covalent organic frameworks (COFs) are a new type of ordered crystalline porous polymers, whose structure can be pre-designed by changing the composition and connection mode of organic monomers. Magnetic COFs make up for the shortcomings of COFs that are difficult to recycle and complicated to operate, and have good application prospects as adsorbents in magnetic solid phase extraction technology. The pre-synthetic modification method refers to the modification before the synthesis reaction of COFs, functionalization of the building blocks of the reaction, and then the synthesis reaction to finally obtain a functionalized product.

[0007] The inventors used the pre-synthesis modification method to achieve the synthesis of covalent organic framework materials. The method is simple to operate and requires mild conditions. With ferroferric oxide as the core of the magnetic nanoparticles, the methyl-functionalized covalent organic framework material was successfully coated on the surface of ferroferric oxide to form a porous organic shell with functional group modification. During the sample pretreatment process, the magnetic nanoparticles were used as magnetic solid phase extractors in complex samples, especially for efficient enrichment of a variety of ferroferric compounds, with good adsorption effect and large adsorption capacity.

[0008] Therefore, according to one aspect of the present invention, the present invention provides a covalent organic framework magnetic nanoparticle. According to an embodiment of the present invention, the magnetic nanoparticle comprises: a core body, the core body is formed by ferrosoferric oxide; a shell, the shell is coated on at least part of the surface of the core body, and the shell is composed of a repeating unit shown in formula I with methyl functionalization.

[0009]

[0010] The covalent organic framework magnetic nanoparticles according to the embodiment of the present invention use ferroferric oxide as the core, have superparamagnetism, and are easy to adsorb and separate, thereby solving the problems of non-magnetic covalent organic framework materials being difficult to separate, difficult to recycle, and complicated to operate due to their low density; the shell is a covalent organic framework material formed by a polycyclic repeating unit of formula I, which is rich in methyl electron-donating groups, has abundant binding sites, and has strong intermolecular forces. The magnetic nanoparticles of the embodiment of the present invention have the advantages of porous and orderly crystal structure, adjustable pore size, large specific surface area and pore size, good stability, high reusability, etc., have broad application prospects in the enrichment of trace harmful substances, are particularly suitable for the extraction of strongly hydrophilic alpha-nonyl compounds in complex samples, significantly shorten the pre-treatment time of the sample, and have a large adsorption amount and a fast adsorption speed. In some embodiments, the adsorption and desorption of alpha-nonyl compounds can be completed in just a few minutes, and have the advantages of simple operation, green environmental protection, and high extraction efficiency.

[0011] In addition, the covalent organic framework magnetic nanoparticles according to the above embodiment of the present invention may also have the following additional technical features:

[0012] According to an embodiment of the present invention, the shell is a porous mesh structure.

[0013] According to an embodiment of the present invention, the average pore diameter of the shell is 2.5-4 nm, and the thickness is 25-35 nm.

[0014] According to an embodiment of the present invention, the specific surface area of ​​the shell is 100-150m 2 ·g -1 .

[0015] According to an embodiment of the present invention, the shell has crystal diffraction peaks at 2θ of 30.22°, 35.56°, 43.18°, 53.68°, 57.16° and 62.74° in X-ray powder diffraction data.

[0016] According to an embodiment of the present invention, the particle size of the core body is 200-300 nm.

[0017] According to an embodiment of the present invention, the saturation adsorption capacity of the magnetic nanoparticles for the raffinate compound is 50-100 mg·g -1.

[0018] According to an embodiment of the present invention, the magnetic nanoparticles may be repeated more than 8 times.

[0019] According to another aspect of the present invention, the present invention provides a method for preparing the aforementioned covalent organic framework magnetic nanoparticles. According to an embodiment of the present invention, the method comprises: contacting an aldehyde monomer and an amino monomer with an organic solvent to obtain a first mixed solution; ultrasonically mixing the first mixed solution with ferroferric oxide nanoparticles to obtain a second mixed solution; and subjecting the second mixed solution to a Schiff base reaction to obtain the magnetic nanoparticles.

[0020] According to the preparation method of the embodiment of the present invention, the shell synthesized by amino monomer and aldehyde monomer is coated on the surface of magnetic ferroferric oxide nanoparticles to form a magnetic covalent organic framework material, which constitutes the shell of the nanoparticles, has superparamagnetism and is easy to be adsorbed and separated, thereby solving the problems of non-magnetic covalent organic framework materials being difficult to separate, difficult to recycle, and complicated to operate due to their low density. At the same time, the prepared shell is rich in methyl electron-donating groups, has abundant binding sites, and has strong intermolecular forces. The magnetic nanoparticles of the embodiment of the present invention have the advantages of porous and orderly crystal structure, adjustable pore size, large specific surface area and pore size, high stability and reusability. In terms of the enrichment of trace harmful substances, it is particularly suitable for the enrichment of strongly hydrophilic ferroferric compounds in complex samples, and has broad application prospects. In addition, the preparation method has simple requirements for experimental equipment, experimental conditions, simple operation, and is green and environmentally friendly and easy to promote and apply.

[0021] According to an embodiment of the present invention, the aldehyde monomer is 1,3,5-tri(4-formylphenyl)benzene (TFPB), and the amino monomer is o-toluidine (OT).

[0022] According to an embodiment of the present invention, the molar ratio of the aldehyde monomer to the amino monomer is 1:1-2, preferably 1:1.5.

[0023] According to an embodiment of the present invention, the mass ratio of the ferrosoferric oxide nanoparticles to the aldehyde monomer is 1:1-2, preferably 1:1.5.

[0024] According to an embodiment of the present invention, the organic solvent is a mixed solution of mesitylene and 1,4-dioxane. Preferably, the volume ratio of the mesitylene to the 1,4-dioxane is 1:1.

[0025] According to an embodiment of the present invention, the ultrasonic mixing time is 30 to 50 minutes.

[0026] According to an embodiment of the present invention, the catalyst of the Schiff base reaction is acetic acid. According to an embodiment of the present invention, the temperature of the Schiff base reaction is 60 to 70 degrees Celsius and the time is 6 to 10 hours.

[0027] According to another aspect of the present invention, the present invention provides a method for adsorbing alpha-type compounds. According to an embodiment of the present invention, the method is performed using the aforementioned magnetic nanoparticles. Thus, the aforementioned magnetic nanoparticles are used for adsorption treatment, and the specificity for alpha-type compounds is high, the adsorption speed is fast, the adsorption capacity is large, the adsorption effect is good, and the operation is simple and fast, which is particularly suitable for the extraction of alpha-type compounds in complex samples; and the method has a short adsorption time and a small amount of magnetic nanoparticles. Only a very small amount of magnetic nanoparticles is needed to complete the adsorption and desorption of alpha-type compounds within a few minutes, which has the advantages of simple operation, green environmental protection, and high extraction efficiency. It should be noted that the magnetic nanoparticles have all the technical features and technical effects of the aforementioned magnetic nanoparticles, which will not be repeated here.

[0028] According to an embodiment of the present invention, the tadalafil compound is at least one selected from tadalafil, aminotadalafil, chlororetadalafil, nortadalafil, N-butyltadalafil, N-octylnortadalafil, acetaminotadalafil, 2-hydroxypropylnortadalafil, N-ethyltadalafil, 2-hydroxyethylnortadalafil, N-phenylpropenyltadalafil and tadalafil dichloro impurity.

[0029] According to an embodiment of the present invention, the saturation adsorption capacity of the magnetic nanoparticles is 50 to 100 mg·g -1 .

[0030] According to an embodiment of the present invention, the adsorption equilibrium time of the magnetic nanoparticles is 20 to 30 minutes.

[0031] According to an embodiment of the present invention, based on 1 mL of liquid sample, the amount of the magnetic nanoparticles used is 0.8-1.2 mg.

[0032] According to an embodiment of the present invention, the extraction time of the method is 3 to 5 minutes.

[0033] According to an embodiment of the present invention, the method is carried out under the condition of pH 6.8-7.2.

[0034] According to an embodiment of the present invention, methanol is used for elution.

[0035] According to an embodiment of the present invention, the elution treatment time is 1.5 to 2.5 minutes.

[0036] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0038] Figure 1 The reaction formula for preparing Fe3O4@TFPB-OT according to one embodiment of the present invention is shown;

[0039] Figure 2 A schematic diagram of characterization of magnetic nanoparticles according to an embodiment of the present invention is shown, wherein: Figure 2 A and Figure 2 B are SEM images of Fe3O4 and Fe3O4@TFPB-OT; Figure 2 C and Figure 2 D are TEM images of Fe3O4 and Fe3O4@TFPB-OT, respectively;

[0040] Figure 3 A schematic diagram of characterization of magnetic nanoparticles according to an embodiment of the present invention is shown, wherein: Figure 3 A is the FT-IR spectrum; Figure 3 B is the X-ray diffraction pattern; Figure 3 C is the thermogravimetric analysis diagram; Figure 3 D is the hysteresis loop diagram; Figure 3 E and Figure 3 F are nitrogen adsorption-desorption isotherm and pore size distribution diagrams, respectively;

[0041] Figure 4 The schematic diagram of magnetic solid phase extraction parameter optimization based on magnetic nanoparticles according to one embodiment of the present invention is shown, wherein Figure 4 A is the optimization diagram of adsorbent dosage; Figure 4 B is the extraction time optimization diagram; Figure 4 C is the solution pH optimization diagram; Figure 4 D is the optimization diagram of elution solvent types; Figure 4E is the optimization diagram of elution solvent volume; Figure 4 F is the elution time optimization diagram;

[0042] Figure 5 A schematic diagram of magnetic nanoparticle adsorption according to an embodiment of the present invention is shown, wherein: Figure 5 A is the static adsorption diagram; Figure 5 B is the dynamic adsorption diagram;

[0043] Figure 6 A schematic diagram showing the reusability results of magnetic nanoparticles according to an embodiment of the present invention is shown. DETAILED DESCRIPTION

[0044] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0045] In the description of the present invention, the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and do not require that the present invention must be constructed and operated in a specific orientation. Therefore, they should not be understood as limitations on the present invention.

[0046] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0047] According to one aspect of the present invention, the present invention provides a covalent organic framework magnetic nanoparticle. The covalent organic framework magnetic nanoparticle according to the embodiment of the present invention uses ferroferric oxide as the core, has superparamagnetism, is easy to adsorb and separate, thereby solving the problems of non-magnetic covalent organic framework materials being difficult to separate, difficult to recycle, and cumbersome to operate due to their low density; the shell is a covalent organic framework material formed by a polycyclic repeating unit of formula I, which has strong hydrophilicity, is rich in methyl-donating groups, has abundant binding sites, has a large specific surface area and pore size, is stable, and has high reusability. It has broad application prospects in the enrichment of trace harmful substances, is particularly suitable for the extraction of strongly hydrophilic alpha-nonyl compounds in complex samples, significantly shortens the sample pre-treatment time, has a large adsorption capacity, and has a fast adsorption speed. In some embodiments, it only takes a few minutes to complete the adsorption and desorption of alpha-nonyl compounds, and has the advantages of simple operation, green environmental protection, and high extraction efficiency.

[0048] According to an embodiment of the present invention, the magnetic nanoparticles include: a core body, which is formed by ferrosoferric oxide; a shell, which covers at least a portion of the surface of the core body, and the shell is composed of a repeating unit shown in Formula I with methyl functionalization.

[0049] According to an embodiment of the present invention, the shell is a porous mesh structure, so that the specific surface area is large and the adsorption capacity is large.

[0050] According to an embodiment of the present invention, the average pore size of the shell is 2.5-4 nm, and the thickness is 25-35 nm, which indicates that the shell is a mesoporous structure, which can form a spatial embedding effect with the target, and is easy to adsorb raffinate compounds, and the shell is thick and has a large adsorption capacity.

[0051] According to an embodiment of the present invention, the specific surface area of ​​the shell is 100-150m 2 ·g -1 Therefore, the specific surface area is large, the adsorption efficiency is high, and the adsorption amount is large.

[0052] According to an embodiment of the present invention, the particle size of the core body is 200-300 nm. Therefore, the particle size of the magnetic nanoparticles is appropriate and the specific surface area is large.

[0053] According to an embodiment of the present invention, the saturation adsorption capacity of the magnetic nanoparticles for the raffinate compound is 50-100 mg·g -1 Therefore, the saturation adsorption capacity of magnetic nanoparticles for raffinate compounds is large.

[0054] According to an embodiment of the present invention, the magnetic nanoparticles can be repeated more than 8 times, and more preferably, can be repeated more than 10 times. As a result, the magnetic nanoparticles can be reused many times and have low cost of use. According to an embodiment of the present invention, in the X-ray powder diffraction data, the shell has crystal diffraction peaks at 2θ of 30.22°, 35.56°, 43.18°, 53.68°, 57.16° and 62.74°. The above group of characteristic peaks matches Fe3O4 with a spinel structure, indicating that the magnetic covalent organic framework has a stable crystal form of Fe3O4, proving the successful synthesis of the magnetic nanoparticles.

[0055] According to another aspect of the present invention, the present invention provides a method for preparing the aforementioned covalent organic framework magnetic nanoparticles. According to the preparation method of the embodiment of the present invention, the shell synthesized by amino monomers and aldehyde monomers is coated on the surface of magnetic ferroferric oxide nanoparticles to form a magnetic covalent organic framework material, which constitutes the shell of the nanoparticles, has superparamagnetism and is easy to adsorb and separate, thereby solving the problems of non-magnetic covalent organic framework materials being difficult to separate, difficult to recycle, and cumbersome to operate due to their low density. At the same time, the prepared shell has the advantages of strong hydrophilicity, methyl-rich electron-donating groups, abundant binding sites, large specific surface area and pore size, high stability and reusability, etc., and is particularly suitable for the enrichment of strongly hydrophilic ferroferric compounds in complex samples in terms of the enrichment of trace harmful substances, and has broad application prospects. In addition, the preparation method has simple requirements for experimental equipment, experimental conditions, simple operation, and is green and environmentally friendly and easy to promote and apply.

[0056] In order to facilitate understanding of the covalent organic framework magnetic nanoparticles of the embodiment of the present invention, the method is explained here. According to the embodiment of the present invention, the method includes:

[0057] S100 Hybrid Contact

[0058] According to an embodiment of the present invention, the aldehyde monomer and the amino monomer are contacted with an organic solvent to obtain a first mixed solution, thereby allowing the aldehyde monomer and the amino monomer to be fully dissolved and contacted in the organic solvent.

[0059] According to an embodiment of the present invention, the aldehyde monomer is 1,3,5-tri(4-formylphenyl)benzene (TFPB), and the amino monomer is o-toluidine (OT). The inventors have rationally designed and selected the monomers used by analyzing the structural characteristics of the alpha-nonyl compounds. Specifically, the parent nucleus of the alpha-nonyl compounds is a derivative of pyrido[3,4-b]pyrazinone. Therefore, the introduction of methyl as an electron donor may change the electron density of the COF material, especially the electron density near the amino group, thereby affecting the electrostatic interaction between molecules; in addition, the introduction of methyl may cause certain parts of the COF framework to form a better spatial structure to adapt to the shape and size of the alpha-nonyl compound molecules, thereby enhancing the matching degree between molecules. Taking the above factors into consideration, the inventors selected OT as the amino monomer. TFPB, as an aldehyde monomer, is rich in benzene ring structure and can produce ππ interaction with the target. At the same time, its structure contains methyl, which can act as an electron donor, and its introduction may change the electron density of the COF material. By analyzing the structural characteristics of the target, a polymer with a specific structure was synthesized using the above-mentioned amino monomer and aldehyde monomer, which was coated on the surface of ferroferric oxide nanoparticles to form a shell material. The resulting magnetic nanoparticles have strong specificity for ferroferric compounds and good adsorption, and are suitable for the enrichment of highly hydrophilic ferroferric compounds in complex samples.

[0060] According to an embodiment of the present invention, the molar ratio of the aldehyde monomer to the amino monomer is 1:1-2, preferably 1:1.5. Thus, at this ratio, the two monomers participating in the reaction can fully react to a greater extent.

[0061] According to an embodiment of the present invention, the organic solvent is a mixed solution of mesitylene and 1,4-dioxane, and preferably, the volume ratio of the mesitylene to the 1,4-dioxane is 1: 1. Thus, with the mixed solvent of mesitylene and 1,4-dioxane (1: 1, v / v) as the solvent, the dispersed phases of ferrosoferric oxide, amino monomers and aldehyde monomers are all good, thereby ensuring full contact of the reaction system, which is conducive to the efficient and sufficient conduct of the reaction.

[0062] S200 Ultrasonic Mixing

[0063] According to an embodiment of the present invention, the first mixed solution is ultrasonically mixed with ferrosoferric oxide nanoparticles to obtain a second mixed solution, thereby forming a dispersed mixed solution.

[0064] According to an embodiment of the present invention, the mass ratio of the ferrosoferric oxide nanoparticles to the aldehyde monomer is 1:1-2, preferably 1:1.5. Thus, this mass ratio is conducive to promoting the smooth progress of the Schiff base reaction.

[0065] According to an embodiment of the present invention, the ultrasonic treatment lasts for 30 to 50 minutes, which is conducive to fully dispersing the amino monomer, the aldehyde monomer and the ferrosoferric oxide nanoparticles in the organic solvent.

[0066] S300 Schiff base reaction

[0067] According to an embodiment of the present invention, the second mixed solution is subjected to a Schiff base reaction to obtain the magnetic nanoparticles. Thus, the amino monomer and the aldehyde monomer form a shell having a repeating unit of formula I on the surface of the ferrosoferric oxide nanoparticles through the Schiff base reaction.

[0068] According to an embodiment of the present invention, the catalyst of the Schiff base reaction is acetic acid, thereby having high catalytic efficiency, which is conducive to the efficient conduction of the Schiff base reaction.

[0069] According to an embodiment of the present invention, the temperature of the Schiff base reaction is 60 to 70 degrees Celsius and the time is 6 to 10 hours, which is conducive to the efficient and sufficient progress of the Schiff base reaction.

[0070] In order to facilitate understanding of the above-mentioned method for preparing the aforementioned covalent organic framework magnetic nanoparticles, a general method for preparing the above-mentioned magnetic nanoparticles is provided herein, which comprises:

[0071] (1) adding aldehyde monomer, amino monomer and ferrosoferric oxide nanoparticles into an organic solvent and dispersing them to form a stable solution;

[0072] (2) subjecting the solution obtained in step (1) to ultrasonic treatment for 30 to 50 minutes;

[0073] (3) slowly adding acetic acid solution as a catalyst to the solution obtained in step (2), controlling the temperature at 60 to 70° C. and performing mechanical stirring, and controlling the temperature of the entire stirring system at 60 to 70° C. to react for 6 to 10 hours to obtain a crude product;

[0074] (4) The crude product obtained in step (3) is mixed with a strong magnet, and washed with methanol and acetonitrile in sequence until the supernatant is clear, and then placed in an oven and dried at 70° C. to obtain covalent organic framework magnetic nanoparticles.

[0075] According to another aspect of the present invention, the present invention provides a method for adsorbing alpha-type compounds. According to an embodiment of the present invention, the method is performed using the aforementioned magnetic nanoparticles. Thus, the aforementioned magnetic nanoparticles are used for adsorption treatment, and the specificity for alpha-type compounds is high, the adsorption speed is fast, the adsorption capacity is large, the adsorption effect is good, and the operation is simple and fast, which is particularly suitable for the extraction of alpha-type compounds in complex samples; and the method has a short adsorption time and a small amount of magnetic nanoparticles. Only a very small amount of magnetic nanoparticles is needed to complete the adsorption and desorption of alpha-type compounds within a few minutes, which has the advantages of simple operation, green environmental protection, and high extraction efficiency. It should be noted that the magnetic nanoparticles have all the technical features and technical effects of the aforementioned magnetic nanoparticles, which will not be repeated here.

[0076] According to an embodiment of the present invention, the tadalafil compound is at least one selected from tadalafil, aminotadalafil, chlororetadalafil, nortadalafil, N-butyltadalafil, N-octylnortadalafil, acetaminotadalafil, 2-hydroxypropylnortadalafil, N-ethyltadalafil, 2-hydroxyethylnortadalafil, N-phenylpropenyltadalafil and tadalafil dichloro impurity.

[0077] According to an embodiment of the present invention, the saturation adsorption capacity of the magnetic nanoparticles is 50 to 100 mg·g -1 Therefore, the magnetic nanoparticles have strong adsorption capacity and large adsorption capacity, and can efficiently extract raffinate compounds from complex samples.

[0078] According to an embodiment of the present invention, the adsorption equilibrium time of the magnetic nanoparticles is 20 to 30 minutes. Therefore, the magnetic nanoparticles have a high adsorption rate and can quickly extract raffinate compounds in complex samples.

[0079] According to an embodiment of the present invention, based on 1 mL of liquid sample, the amount of magnetic nanoparticles used is 0.8-1.2 mg. Therefore, the amount of magnetic nanoparticles used is reasonable, which is conducive to the full extraction of raffinate compounds in the liquid sample and avoids excessive use of magnetic nanoparticles.

[0080] According to an embodiment of the present invention, the extraction time of the method is 3 to 5 minutes. Thus, the extraction recovery rate of raffinate compounds tends to be stable.

[0081] According to an embodiment of the present invention, the method is carried out under the condition of pH 6.8-7.2. Thus, the extraction recovery rate of raffinate compounds is high.

[0082] According to the embodiment of the present invention, methanol is used for elution treatment, thereby achieving high elution efficiency and high recovery rate of raffinate compounds.

[0083] According to an embodiment of the present invention, the elution treatment time is 1.5 to 2.5 minutes, which is conducive to the full elution of the raffinate compounds.

[0084] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and should not be construed as limiting the present invention.

[0085] Below in conjunction with embodiment, the scheme of the present invention will be explained.It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.Unrepresented specific techniques or conditions in the embodiment, according to the technology or conditions described in the document in this area or according to the product specification sheet.Reagents used or instruments that do not indicate manufacturers are conventional products that can be obtained commercially, for example, can be purchased from Sigma company.

[0086] Example 1

[0087] In this embodiment, 1,3,5-tri(4-formylphenyl)benzene (TFPB) is used as an aldehyde monomer and o-toluidine (OT) is used as an amino monomer to prepare a magnetic covalent organic framework. The specific method is as follows:

[0088] (1) The monomers 1,3,5-tri(4-formylphenyl)benzene (0.3 mmol, 117 mg) and o-tolidine (0.45 mmol, 95.4 mg) were dissolved in 22 mL of a mixed solvent of mesitylene and 1,4-dioxane (1:1), and ferrosoferric oxide nanoparticles (with a mass ratio of 1:1.5 to the aldehyde monomer) were added, and ultrasonic oscillation was performed for 30 min;

[0089] (2) The above solution was then mechanically stirred in a water bath, the temperature was controlled at 65° C., and the speed was controlled at 550 rpm to ensure that the entire stirring system was completely mixed, 2 mL of acetic acid solution was slowly added dropwise as a reaction catalyst, and the entire system was kept at 65° C. for 8 hours to obtain a crude product;

[0090] (3) The crude product was repeatedly washed with methanol and acetonitrile by a strong magnet until the supernatant was clear, and then dried in an oven at 70°C for 12 h to obtain magnetic gray powder particles Fe3O4@TFPB-OT. The reaction formula is as follows: Figure 1 .

[0091] Example 2

[0092] A detailed characterization experiment was conducted on the magnetic covalent organic framework nanomaterial (Fe3O4@TFPB-OT) prepared in Example 1 to demonstrate the successful preparation of the methyl functionalized magnetic nanomaterial and its excellent physical and chemical properties. The specific contents are as follows:

[0093] 1. The morphology and internal structure of Fe3O4 nanomaterials and methyl functionalized magnetic covalent organic framework materials (Fe3O4@TFPB-OT) were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. Figure 2 A and Figure 2 As shown in Figure B, the structures of Fe3O4 nanomaterials and Fe3O4@TFPB-OT are both regular monodisperse spheres. Figure 2 As can be seen in D, Fe3O4@TFPB-OT has an obvious core-shell structure, and the inner black core is Fe3O4, indicating that the adsorbent has good magnetic properties. The outer light gray coating is the TFPB-OT coating, which is similar to Figure 2 Compared with Fe3O4 with C, the shell thickness of Fe3O4@TFPB-OT is about 55nm, indicating that Fe3O4@TFPB-OT was successfully synthesized on the surface of the magnetic core.

[0094] 2. The chemical structure and composition of Fe3O4 and magnetic nanoparticles Fe3O4@TFPB-OT were analyzed by Fourier transform infrared spectroscopy. Figure 3 As shown in A, the transmittance range is from 4000 to 500 cm -1 In the spectrum of Fe3O4, 566.3cm -1 The peak at 1686 cm indicates the existence of Fe-O-Fe stretching vibration; in the spectra of monomers TFPB and OT, -1 and 3468cm -1 The characteristic peaks at 566 cm-1 come from the stretching vibration of -CHO and -NH2 respectively. Compared with the spectra of the two monomers TFPB and OT, the spectrum of Fe3O4@TFPB-OT has a peak at 566 cm-1. -1 There is an obvious adsorption band at 1596 cm, which is attributed to the Fe-O-Fe vibration of Fe3O4 nanoparticles, indicating that the methyl functionalized framework material is successfully coated on Fe3O4. -1 and 3433cm -1Two characteristic peaks appeared at , which were related to the stretching vibrations of C=N and NH, indicating that a polycondensation reaction occurred between the two monomers, further proving the successful synthesis of Fe3O4@TFPB-OT.

[0095] 3. If Figure 3 As shown in Figure B, the crystallinity and structure of the synthesized Fe3O4 and Fe3O4@TFPB-OT were characterized by XRD patterns. The same characteristic diffraction peaks as those of Fe3O4 can be observed at 10-80° for Fe3O4@TFPB-OT, which are at 30.22°, 35.56°, 43.18°, 53.68°, 57.16° and 62.74°, respectively. These peaks are consistent with the spinel contained in Fe3O4, thus proving that the covalent organic framework coating (TFPB-OT) is successfully coated on the outer surface of Fe3O4, and Fe3O4@TFPB-OT still retains a good crystal structure during the synthesis process.

[0096] 4. In order to explore the stability of Fe3O4@TFPB-OT under high temperature conditions, the mass change of Fe3O4@TFPB-OT under temperature changes from 0 to 800℃ was studied by thermogravimetric analyzer. The results are as follows: Figure 3 As shown in Figure C, when the temperature rises to 400°C, the weight loss of Fe3O4@TFPB-OT is 1.18wt%, which is not obvious. As the temperature continues to rise, Fe3O4@TFPB-OT loses 20.19wt% of its weight at 400-800°C. This phenomenon reveals that the weight loss of COF shell is caused by the poor stability of organic monomers. Therefore, according to the TGA curve, it can be concluded that Fe3O4@TFPB-OT has good thermal stability below 400°C.

[0097] 5. The magnetic properties of Fe3O4@TFPB-OT were evaluated using a vibrating sample magnetometer (VSM). Figure 3 As shown in D, the saturation magnetization of Fe3O4 and Fe3O4@TFPB-OT are 85.19 and 31.16 emu·g, respectively. -1 It can be clearly seen in the figure that due to the formation of a COF coating on Fe3O4 by the magnetic covalent organic framework material, its magnetism is reduced, but it can still be quickly separated in the solution within 15s under the action of an external magnetic field. The high saturation magnetization intensity of Fe3O4@TFPB-OT is sufficient to meet the requirements of separation from the sample matrix solution.

[0098] 6. Figure 3 E and Figure 3F is the nitrogen adsorption-desorption isotherm and pore size distribution of Fe3O4@TFPB-OT. It can be inferred from the figure that Fe3O4@TFPB-OT has a mesoporous structure. In addition, the Brunauer-Emmet-Teller specific surface area and pore size are 119.20 m 2 ·g -1 (Refer to the specific surface area of ​​Fe3O4, which is 7.00 m 2 ·g -1 ) and 3.09 nm, the larger specific surface area and pore size are conducive to the efficient enrichment of the target by Fe3O4@TFPB-OT.

[0099] Example 3

[0100] In this embodiment, the magnetic nanoparticles prepared in Example 1 were used to perform solid phase extraction on 12 kinds of raffinate compounds. The difference was that the amount of Fe3O4@TFPB-OT, extraction time, extraction solution pH, elution solvent type, elution time and elution volume were changed respectively, and the effects of different magnetic solid phase extraction conditions on the extraction recovery rate were investigated respectively. Specifically, the effects of the amount of magnetic nanoparticles Fe3O4@TFPB-OT (1-10 mg), extraction time (1-15 min), extraction solution pH (3-11), elution solvent (methanol, ethanol, acetonitrile, acetone), and elution time (0.5-5 min) on the extraction recovery rates of 12 kinds of raffinate compounds were investigated respectively. The specific operation is as follows:

[0101] (1) Accurately weigh 5.0 mg of Fe3O4@TFPB-OT fraction and place it in 5 mL of beverage sample solution, which is rapidly vortexed on a multi-tube vortexer (1800 r / min) for 7 min, and the supernatant is discarded with the help of an external magnet;

[0102] (2) Add 32 mL of methanol eluent to the precipitate and elute the raffinate compounds by ultrasonication for 2 min.

[0103] (3) With the help of an external magnet, Fe3O4@TFPB-OT was separated from the eluent, and the eluent was transferred to a nitrogen blowpipe and blown to near dryness under nitrogen at 35 °C.

[0104] (4) Add 1 mL of methanol for re-dissolution, filter through a 0.22 μm filter membrane, and finally detect using HPLC-MS / MS.

[0105] All experiments were set up in triplicate, and the results were averaged. The error bars after the plots represent the standard deviation between the parallel data.

[0106] The experimental results are as follows Figure 4 As shown in A-4F, specifically, Figure 4As shown in A, when the dosage of Fe3O4@TFPB-OT is 5 mg, the extraction recovery rates of the four raffinate compounds tend to be stable, reaching 55-95%, indicating that only a small amount of adsorbent is needed to achieve efficient enrichment; Figure 4 As shown in Figure B, when the extraction time was 4 min, the extraction recoveries of the 12 raffinate compounds tended to be stable; Figure 4 As shown in C, when the pH is 7, the extraction recovery rate of 12 raffinate compounds reaches the highest; Figure 4 As shown in D, the elution efficiency of 12 raffinate compounds by different organic solvents varies greatly. When methanol is used as the elution solvent; Figure 4 As shown in E, when the elution volume is 2 mL, the extraction recovery rates of 12 raffinoid compounds are relatively ideal; Figure 4 As shown in Figure F, when the elution time was 2 min, the extraction recoveries of the 12 raffinate compounds tended to be stable.

[0107] In summary, the magnetic covalent organic framework of the embodiment of the present invention as a magnetic solid phase extraction adsorbent has the advantages of small amount of material, short extraction time, small amount of organic reagent, high reusability, simple operation, etc., and has broad application prospects.

[0108] Example 4

[0109] The magnetic nanoparticles (Fe3O4@TFPB-OT) prepared in Example 1 were used to study their adsorption behavior on 12 kinds of raffinate compounds, as follows:

[0110] The adsorption performance of Fe3O4@TFPB-OT prepared in Example 1 on different concentrations of raffinate compounds at different times was studied by adsorption isotherm and adsorption kinetics experiments. For the adsorption isotherm experiment, 0.5 mg of Fe3O4@TFPB-OT was added to 2 mL of 12 different concentrations of raffinate compounds in aqueous solution (5, 10, 20, 30, 40, 50, 60, 70, 80 mg·L -1 ) and vortexed for 2 h to allow the adsorbent to fully contact the target. The adsorption capacity of raffinate compounds on Fe3O4@TFPB-OT adsorbent was studied. Assuming the mass of the adsorbent is m (mg), the volume of the solution is V (mL), and the initial concentration of the target is C0 (μg mL -1 ). At a certain time (t) in the solution, the concentration of the target substance is Ce (μg·mL -1 ), ignoring the change in solution volume, the adsorption capacity of Fe3O4@TFPB-OT can be calculated using the following formula:

[0111]

[0112] For the adsorption kinetics experiment, 0.5 mg of Fe3O4@TFPB-OT was added to 2 mL of 12 raffinate solutions (50 μg mL -1 ) and vortexed to allow adsorption at different times (1 min, 5 min, 10 min, 20 min, 40 min, 60 min). The results of this embodiment are still calculated by formula (1) for the maximum adsorption capacity of Fe3O4@TFPB-OT for 12 kinds of raffinate compound solutions.

[0113] The static equilibrium adsorption curves of Fe3O4@TFPB-OT for 12 raffinate compounds at different initial concentrations are shown in Figure 2. Figure 5 As shown, from Figure 5 It can be seen that when the dosage of the adsorbent is 1.0 mg, the adsorption capacity of the magnetic adsorbent for raffinate compounds is between 0 and 80 μg mL -1 The concentration range was gradually increased and at 50 μg mL -1 The adsorption equilibrium was reached when the adsorption was carried out. The experimental maximum adsorption capacities of tadalafil, aminotadalafil, tadalafil methyl chloride, demethyl tadalafil, N-butyl tadalafil, N-octyl demethyl tadalafil, acetamido tadalafil, 2-hydroxypropyl demethyl tadalafil, N-ethyl tadalafil, 2-hydroxyethyl demethyl tadalafil, N-phenylpropenyl tadalafil and tadalafil dichloro impurity were calculated to be 90.9, 53.8, 88.5, 89.3, 86.2, 62.9, 84.0, 83.3, 87.2, 87.0, 52.4 and 88.4 mg·g, respectively. -1 The dynamic equilibrium adsorption curves of Fe3O4@TFPB-OT for 12 raffinate compounds at different adsorption times are shown in Figure 2. Figure 5 As shown in B. As can be seen from the figure, the adsorption of 12 kinds of raffinate compounds by Fe3O4@TFPB-OT is a rapid adsorption process, and the adsorption equilibrium is reached in 20 to 30 minutes. Fe3O4@TFPB-OT has a large adsorption capacity for 12 kinds of raffinate compounds and reaches adsorption equilibrium in a short time. This may be attributed to the fact that Fe3O4@TFPB-OT has abundant methyl-rich electron-donating groups, binding sites, high hydrophilicity, large specific surface area and pore size, and there are methyl-rich electron-donating groups between raffinate compounds, interaction forces, hydrophilic interaction forces, electrostatic interaction forces, π-π interactions, etc. These results show that Fe3O4@TFPB-OT has good adsorption performance for 12 kinds of raffinate compounds.

[0114] Example 5

[0115] Evaluating the reusability of materials is of great significance for evaluating the excellent performance of adsorption materials and improving the application potential of Fe3O4@TFPB-OT. In this example, the used adsorbent was recycled, methanol and acetonitrile were used as cleaning solvents, and ultrasonic cleaning was performed several times to ensure that no target analyte remained on the adsorbent. Figure 6 As shown, the extraction recovery rate of the adsorbent for raffinate compounds remained basically unchanged after being reused 10 times. This shows that the adsorbent can be used at least 10 times, verifying its good usability and stability.

[0116] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0117] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A covalent organic framework magnetic nanoparticle, characterized in that: include: A core body, wherein the core body is formed of ferroferric oxide; A shell is coated on at least a portion of the surface of the core, and the shell is composed of a repeating unit of formula I functionalized with methyl groups.

2. The magnetic nanoparticle according to claim 1, characterized in that The shell is a porous mesh structure. Optionally, the shell has an average pore size of 2.5 to 4 nm and a thickness of 25 to 35 nm. Optionally, the specific surface area of ​​the shell is 100 to 150 m 2 ·g -1 .

3. The magnetic nanoparticles according to claim 1, characterized in that The particle size of the core body is 200-300 nm.

4. The magnetic nanoparticle according to claim 1, characterized in that In X-ray powder diffraction data, the shell has crystal diffraction peaks at 2θ of 30.22°, 35.56°, 43.18°, 53.68°, 57.16° and 62.74°.

5. A method for preparing the covalent organic framework magnetic nanoparticles according to any one of claims 1 to 4, characterized in that: include: contacting the aldehyde monomer and the amino monomer with an organic solvent to obtain a first mixed solution; Ultrasonic mixing the first mixed solution with ferroferric oxide nanoparticles to obtain a second mixed solution; as well as The second mixed solution is subjected to a Schiff base reaction to obtain the magnetic nanoparticles.

6. The method according to claim 5, characterized in that The aldehyde monomer is 1,3,5-tri(4-formylphenyl)benzene, and the amino monomer is o-toluidine. Optionally, the molar ratio of the aldehyde monomer to the amino monomer is 1:1-2, preferably 1:1.

5. Optionally, the mass ratio of the ferrosoferric oxide nanoparticles to the aldehyde monomer is 1:1-2, preferably 1:1.

5. Optionally, the organic solvent is a mixed solution of mesitylene and 1,4-dioxane. Preferably, the volume ratio of the mesitylene to the 1,4-dioxane is 1:

1.

7. The method according to claim 5, characterized in that The ultrasonic mixing time is 30 to 50 minutes.

8. The method according to claim 5, characterized in that The catalyst for the Schiff base reaction is acetic acid, Optionally, the temperature of the Schiff base reaction is 60 to 70 degrees Celsius and the time is 6 to 10 hours.

9. A method for adsorbing raffinate compounds, characterized in that: The method is carried out using the magnetic nanoparticles described in any one of claims 1 to 4.

10. The method according to claim 9, characterized in that The tadalafil compound is at least one selected from tadalafil, aminotadalafil, tadalafil methyl chloride, demethyl tadalafil, N-butyl tadalafil, N-octyl demethyl tadalafil, acetamido tadalafil, 2-hydroxypropyl demethyl tadalafil, N-ethyl tadalafil, 2-hydroxyethyl demethyl tadalafil, N-phenylpropenyl tadalafil and tadalafil dichloro impurity. Optionally, the saturation adsorption capacity of the magnetic nanoparticles is 50 to 100 mg·g -1 , Optionally, the adsorption equilibrium time of the magnetic nanoparticles is 20 to 30 minutes. Optionally, based on 1 mL of liquid sample, the amount of the magnetic nanoparticles used is 0.8 to 1.2 mg. Optionally, the extraction time of the method is 3 to 5 minutes, Optionally, the method is carried out at pH 6.8 to 7.2, Optionally, elution with methanol is performed, Optionally, the elution treatment time is 1.5 to 2.5 minutes.